Applying SIMO combining in V2X communcations, performance measurements and comparisons - Dayana Jamaludin (2015)
Dedicated short range communication (DSRC) is a technology that has been explored in the recent years to combat the large number of accidents arising from vehicle collision. In the Global status report on road safety 2013 by the World Health Organization (WHO), it was stated that the number of deaths and injuries caused by road accidents was 1.24 million and 20 to 50 million respectively. DSRC is a technology used for vehicular communication applications. It has a designated licensed bandwidth primarily allocated for vehicle safety application. Some examples of the vehicular communication applications include collision prevention, navigation application for places without GPS and toll collection. The main objectives of this project are to apply multiple input multiple output (MIMO) coding techniques to DSRC radio, measuring link reliability and communication performance and comparing performance using different types of MIMO antenna configurations. The report covers the results obtained which were the maximum transmission distances for the different modulation and coding schemes, the effect of the environment on DSRC communication performance and also the simulation results of applying the SIMO combining techniques on a constructed DSRC channel.